Question

Sinfe,
Now, Use
( begin{aligned} x^{4}+x^{2}+1 &=left(x^{2}+x+1right)left(x^{2}+x+1right) frac{2 x}{x^{4}+x^{2}+1} &=frac{2 x}{left(x^{2}+x+1right)left(x^{2}-x+1right)} &=frac{left(x^{2}+x+1right)-left(x^{2}-x+1right)}{left(x^{2}-x+1right)left(x^{2}+x+1right)} &=frac{left(x^{2}+x+1right)}{left(x^{2}+x+1right)left(x^{2}-x+1right)}-frac{left(x^{2}-x+1right)}{left(x^{2}+x+1right)left(x^{2}+4+1right)} &=frac{1}{x^{2}-x+1}-frac{1}{x^{2}+x+1} end{aligned} )

# 1. 2x at tx? +1 (b) *-1_ +1 x-x+1 2+x-1 x +1 x2-x+1 x² + x-1 + - ( la) x2 - x+1 x² + x +1

Solution